Bilateral Optic Disc Swelling Following Anastrozole Therapy. (October 2014) - Coppes, Oscar Jim Michael; Lukas, Rimas V.; Fleming, Gini F.; Nichols, Jeffrey; Tenney, Meaghan; Bernard, Jacqueline
Abstract A 56-year-old female with early-stage breast cancer, stage IA grade 1 endometrial cancer, and stage IC grade 1 ovarian cancer developed sudden-onset visual changes and right inferior visual field defect following anastrozole therapy. Examination revealed severe bilateral optic disc swelling and impaired visual acuity. Laboratory work-up was otherwise unremarkable. Anastrozole was discontinued and over the next month, patient had near-complete resolution of swelling in the right eye and improvement in the left eye. This is the only reported case of optic disc swelling following anastrozole therapy.